A Physical Geography Theory of the Different Origins of Western and Eastern Civilizations - Hanwen, Mi (Technium Social Sciences Journal, 2022)
The idea that the common ancestor of the human family originated on the African continent about 7 to 5 million years ago is not much disputed by the academic community. However, humans who originated from the same place are nowadays very different. Due to historical origins, customs and living environment, not only are there huge differences in skin color, physique and appearance, but also cultural differences. As the saying goes, one side of the land nurtures one side of the people, and the difference in the geographical environment makes people from different regions not only different from other regions in terms of physiology but also significantly different in terms of culture and psychology. In this paper, we start with the difference in the geographical environment and analyze its influence on the religious, written aspects and science of Eastern and Western cultures. Thus, the conclusion that geographical differences are the root cause of the cultural differences between East and West is drawn to promote economic and cultural exchanges between East and West, and thus better promote the development of world culture.